Cation-induced coagulation in graphene oxide suspensions. (September 2019) - Wen, X.; Jin, X.; Wang, F.; You, Y.; Chu, D.; Zetterlund, P.B.; Joshi, R.K.
Abstract: Graphene oxide (GO) offers excellent multifunctional properties with potential for applications. The applicability depends on the stability of GO suspensions in different mediums. Herein, we report a systematic study of cation-induced coagulation phenomenon in GO suspension in water. We have investigated the morphology of coagulated GO, coagulation degree of GO suspensions, and the factors affecting coagulation process. Our study suggests that the coagulation of GO depends on concentration of cations, surface charge, and coordination bond energy of cations introduced into the suspensions. This study helps us understand the coagulation phenomenon in GO suspension, and it will be helpful in preparing GO with 3-dimensional porous structure with improved surface area for applications. Highlights: Cation-induced coagulation in graphene oxide suspension is studied. Coagulation of GO depends on concentration, surface charge, and coordination bond energy of introduced cations. Coagulation in GO suspension can be helpful in preparing 3-dimensional porous GO with the improved surface area.